Paractinolaimus persicus sp. n. (Nematoda: Actinolaimidae) from Iran - Panahi, Hadi; Shokoohi, Ebrahim; Vinciguera, Maria T; Clausi, Mirella; Mashela, Phatu. W. (Zootaxa, 2019)
A new species of the genus Paractinolaimus, namely, Paractinolaimus persicus sp. n., is described. It is characterised by body 2.3–2.6 mm long; low, truncate lip region; four massive, acute onchia; stoma walls covered with sparse tiny denticles; odontostyle 25–28 μm long; well developed, didelphic-amphidelphic female reproductive apparatus; vulva a longitudinal oval pore; absence of advulval papillae; female tail 146–224 µm long (c’ = 3.3–5.9), elongated filiform, curved ventrad, and with acute terminus; male tail convex conoid with blunt terminus; and 17–18 nearly contiguous ventromedian supplements. This species was recovered from the rhizosphere of wild grass. Line drawings, LM and SEM photographs and measurements are provided.